Comprehensive Review of Transdermal Drug Delivery Systems: Mechanisms, Materials, and Modern Innovations - Patil Vaishnavi D; Dr. Gosavi Sheetal B (Asian Journal of Pharmaceutical Research and Development, 2025)
Transdermal Drug Delivery Systems (TDDS) provide an innovative and non-invasive route for controlled and sustained drug administration through the skin. This review highlights the historical development, formulation components, classification, evaluation parameters, and regulatory perspectives of TDDS. Advantages such as bypassing first-pass metabolism, maintaining consistent plasma levels, and improving patient compliance are emphasized, along with challenges like limited permeability and skin irritation. Furthermore, emerging technologies including nanocarriers, molecularly imprinted polymers, microneedles, and 3D-printed systems are discussed for their potential to enhance drug permeation and therapeutic efficacy. Overall, TDDS continue to evolve as efficient, patient-oriented alternatives to conventional dosage forms.